PENGARUH PIJAT BAYI TERHADAP PENINGKATAN MOTORIK KASAR PADA BAYI USIA 6-12 BULAN DI PACARKELING HOME CARE KEJAYAN, PASURUAN - Nikmatullailia, Firda; Alfitri, Rosyidah; Widiatril, Raden Maria Veronika (NHM PRESS, 2024)
The baby's growth and development period is a golden period as well as a critical period for a person's development, namely at the age of 0-12 months. It is said to be the golden age because infancy is very short and cannot be repeated. It is said to be a critical period because during this period babies are very sensitive to the environment and need good nutritional intake and stimulation for their growth and development. As a result of gross motor skills that are not optimal, children's creativity in adapting can decrease. According to Hurlock, motor skills are also used for self-help skills (self-image), social skills, play skills and school skills. To achieve independence, children must learn motor skills that enable them to do things for themselves, so that they can become a cooperative social group that can be accepted in their environment. This research design is an experimental design, with a one group pretest - posttest design approach, namely by taking measurements before and after treatment. Then intervention was given by giving the baby massage after the post test was carried out. The aim is to analyze the effect of baby massage on gross motor skills in babies aged 6-12 months.That the age of babies in the Kejayan village area, Pasuruan Regency, in the group that was given massage, babies aged 6 months were 2 respondents (13%), babies aged 8 months were 3 respondents (20%), babies aged 9 months were 3 respondents (20 %), babies aged 10 months were 6 respondents (40%), and babies at 11 months were 1 respondent (7%). In the group that was not given massage, 6 month old babies were 1 respondent (7%), 8 month old babies were 2 respondents (13%), 9 month old babies were 2 respondents (13%), 10 month old babies as many as 7 respondents (47%), for babies aged 11 months there were 3 respondents (20%). Gross motor development in babies aged 6-12 months who were given baby massage in Kejayan Village, Pasuruan Regency is mostly normal.